Optic antics : the cinema of Ken Jacobs - Pierson, Michele; James, David E., 1945-; Arthur, Paul, 1947-2008. (New York : Oxford University Press, 2011)
1. Introduction: Ken Jacobs-A Half-Century of Cinema##- 2. "A Panorama Compounded of Great Human Suffering and Ecstatic Filmic Representation": Texts On Ken Jacobs##- 3. Texts On Ken Jacobs##- 4. A Mischievous Little-Boy Revolution: The Whirled##- 5. Ken Jacobs, Moralist##- 6. The Sky Socialist: Film as an Instrument of Thought, Cinema as an Augury of Redemption##- 7. Bigger Than Life: Between Ken Jacobs and Nicholas Ray##- 8. Acts of Delay: The Play between Stillness and Motion in Tom, Tom the Piper's Son##- 9. The Piper's Son: Content and Performance in the Films of Ken Jacobs##- 10. Ken Jacobs' Two Wrenching Departures##- 11. Photo Essay##- 12. Flo Talks##- 13. Recycling, Visual Study, Expanded Theory - Ken Jacobs, Theorist, or: The Long Song of the Sons##- 14. "Avant-Garde" Filmmaker: Ken Jacobs##- 15. Ken Jacobs and the Robert Flaherty Seminar##- 16. Nervous Ken: XCXHXEXRXRXIXEXSX and after##- 17. Jacobs' Bergsonism##- 18. Ken Jacobs and Ecstatic Abstraction##- 19. Busby Berkeley, Ken Jacobs: A Precarious, Extravagant, Populist, and Constructivist Cinema##- 20. Untitled (for Ken)##- 21. Theories of Moving Pictures: Ken Jacobs after Hans Hofmann##- 22. I Owe Ken Jacobs##- 23. Professor Ken##- 24. Annotated Filmography and Performance History##- 25. Bibliography
Includes bibliographical references and index.
boek
Keywords: Jacobs, Ken, -- 1933- -- Criticism and interpretation